Space use by semi‐free‐ranging cows on wetlands and its implication as a conservation management tool. Issue 3 (6th September 2021) - Mirski, Paweł
Abstract : Wetlands are often exposed to reed and shrub expansion that dominate their heterogeneous landscape and threaten species inhabiting open wetlands. The alternative to heavy‐machine mowing is grazing, which should be carried out without fencing in high‐value protected areas. To evaluate the effectiveness of semi‐free‐ranging cattle in sustaining and restoring the open landscape of heterogeneous wetlands in Biebrza National Park, a herd of semi‐free‐ranging dairy cows was followed with a GPS tag. Cows freely grazed for 10.7 hours, on average, during the day and were taken to a cowshed at night. Each day the herd moved 10.2 km, on average (up to 23.5 km), but usually stayed in the radius of 3.5 km (up to 4.7 km) from the cowshed. The core foraging range (50% kernel) reached 46 ha (stock density reached 0.63 cow/ha), but the total foraging range (95% kernel) was a few times larger—208 ha (0.14 cow/ha). The cows used all available habitats (fen grasslands, hillocks, trees, and shrubs), but avoided reed in the late summer and autumn as well as afforested sites in spring. On the whole, reed expansion was suppressed in the cows' foraging range, while it still continued to increase on the outskirts of the study area, where cows did not regularly graze. It can be concluded that semi‐free‐ranging cattle can be used to effectively impede reed succession within a large wetland area.